2020
DOI: 10.1016/j.neo.2020.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-wide DNA methylation profiling of portal vein tumor thrombosis (PVTT) tissues in hepatocellular carcinoma patients

Abstract: Aberrant methylation is a hallmark of hepatocellular carcinoma and plays an important role in tumor initiation and progression. However, the epigenome-wide methylation patterns of portal vein tumor thrombosis (PVTTs) have not been fully explored. Here, we performed epigenome-wide DNA methylation of adjacent normal tissues (ANTs), paired tumor tissues and paired PVTTs using an Infinium HumanMethylation450 array ( n = 11) and conducted the Sequenom EpiTYPER assays to confirm the aberrantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
(48 reference statements)
2
8
0
Order By: Relevance
“…The results of alternation occurrence analysis and intergenic correlation analysis implied the DEGs correlated with each other closely ( Figure 7A and Supplementary Table 3 ). And the DEGs’ co-expressive genes were mostly involved in ECM organization, focal adhesion, along with the binding of integrin and collagen ( Figure 7 ), which was consistent with the previous studies [ 14 , 16 ]. As we know, the TME is formed by cellular components (stroma cells, immune cells, and endothelial cells, etc.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of alternation occurrence analysis and intergenic correlation analysis implied the DEGs correlated with each other closely ( Figure 7A and Supplementary Table 3 ). And the DEGs’ co-expressive genes were mostly involved in ECM organization, focal adhesion, along with the binding of integrin and collagen ( Figure 7 ), which was consistent with the previous studies [ 14 , 16 ]. As we know, the TME is formed by cellular components (stroma cells, immune cells, and endothelial cells, etc.…”
Section: Discussionsupporting
confidence: 90%
“…These genes participated in focal adhesion and xenobiotics metabolism, and many of them could regulate the invasion of HCC cells [ 13 ]. Besides, genomic variations [ 12 ], non-coding RNAs [ 10 , 15 ], DNA methylation [ 16 ], cancer stem cells [ 17 ], along with the immune cells [ 18 ] and vascular endothelial cells [ 19 ] in the tumor microenvironment (TME) have been reported to contribute to the development of PVTT.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, patients with increased C8orf76 had worse OS in the TCGA dataset (Figure 1C). Moreover, we also found that C8orf76 was highly expressed in tumor and portal vein tumor thrombosis (PVTT) tissues compared to adjacent benign tissues according to our previous RNA-seq analysis [24] (Figure 1D).…”
Section: C8orf76 Expression Was Enhanced In Hcc Patients and Related ...supporting
confidence: 64%
“…37 Other factors such as the vascular endothelial cells, immune cells in the tumor microenvironment, genomic irregularities, sequential alterations of mRNA expression, DNA methylation of differentially expressed genes, cancer stem cells, dysregulation of extracellular matrix organization, and focal adhesion have all been proposed to contribute to the development of PVTT. [38][39][40][41] HBV infection and active replication has also been implicated in the vascular invasion in HCC patients. 42 Figure 1 Management of advanced hepatocellular carcinoma according to different guidelines.…”
Section: Risk Factors For Pvtt Formationmentioning
confidence: 99%